Makna kenyamanan dan keamanan dari perspektif penghuni rumah - Danti Arinta Hapsari; Hanson Endra Kusuma; Rizki Dwika Aprilian; Allis Nurdini (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Currently, the design of unfenced houses is an option that is equal to the number of people who prefer fenced houses. The preference of housing design has various qualities and environmental disturbances that have impacts on the comfort and security felt by occupants. This study aims to identify the meaning of comfort and security from occupant’s perspective against the choosing of housing concept. The research was carried out in two steps, the first step was performed qualitatively with an open-ended questionnaire. The second step of research was continued quantitatively by collecting data using an online questionnaire with close-ended questions. The results of the data collected were analyzed using factor analysis and multivariate regression analysis. The final result of the research found that the presence of a fenced or unfenced did not affect the meaning of comfort and security in the dwellings. Factors from environmental disturbances also did not affect the comfort and safety of occupants in choosing the type of housing where occupants already understand the situation that is being completely limited. This is very closely related to the pandemic situation when the research was carried out. The meaning of comfort and security is more influenced by the ability of the occupants themselves to adapt doing activities in their homes or in their territorial environment.